THE INFLUENCE OF THE ANGLE OF ATTACK ALPHA ON THE PRESSURE RECOVERY AT AERODYNAMICS INTERFACE PLANE INVESTIGATION - Subagyo, Subagyo (BRIN Publishing, 2019)
In the process of design, anaircraft to know the performance and stability requires testing in a wind tunnel.Similarly, the selection of engines for aircraft design embedded on conducted tests in a wind tunnel model air intake with some variation of the angle of attack.This paper examines the effect ofthe high angle of attack alpha testing aircraft air intake with a position of beta 0Â° on the subsonic regime with wind speeds of 65 ms-1.Â Combat aircraft flying with an unexpected manoeuvre to avoidenemy attack nor did defence against missiles.Often the aircraft must fly to the position of a very high angle of attack.The theoretical value of the Pressure Recovery is approaching one in order to make the machine pinned can work optimally.Experimental observations of Pressure Recovery plotted against the variation of the angle of attack alpha.The observations show the performance design of aircraft engine inlet on the angle of attack alpha large can still give adequate pressure recovery.